2022
DOI: 10.3390/ijerph191710719
|View full text |Cite
|
Sign up to set email alerts
|

“You Don’t Look Dyslexic”: Using the Job Demands—Resource Model of Burnout to Explore Employment Experiences of Australian Adults with Dyslexia

Abstract: Background: Employment and job security are key influences on health and wellbeing. In Australia, little is known about the employment lifecycle of adults with dyslexia. Materials and Methods: Using a qualitative research design, this study sought to explore the experiences faced by adults with dyslexia seeking and retaining employment. In-depth interviews were conducted with a cohort either currently or previously in the labour market. We used the Job Demands Resource Model of Burnout (JD-R Model) to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 87 publications
1
21
0
Order By: Relevance
“…Employment difficulties were a particular concern for many of the adults in our study and were linked to mental health concerns via quality-of-life (e.g., worries about financial security), bullying/discrimination, concerns about disclosure, and/or exhaustion due to masking/compensating for language difficulties at work. Dyslexic and autistic adults have reported that employment doesn't necessarily correlate with better mental health in the same way as it does in the general population (50)(51)(52) and highlight similar experiences of discrimination, fatigue, and working under personal or psychological strain as explanatory factors (50,52,53). Future research into facilitators and barriers to positive employment experiences for adults with DLD is needed if we are to better support the mental health and wellbeing of adults with DLD.…”
Section: Discussionmentioning
confidence: 99%
“…Employment difficulties were a particular concern for many of the adults in our study and were linked to mental health concerns via quality-of-life (e.g., worries about financial security), bullying/discrimination, concerns about disclosure, and/or exhaustion due to masking/compensating for language difficulties at work. Dyslexic and autistic adults have reported that employment doesn't necessarily correlate with better mental health in the same way as it does in the general population (50)(51)(52) and highlight similar experiences of discrimination, fatigue, and working under personal or psychological strain as explanatory factors (50,52,53). Future research into facilitators and barriers to positive employment experiences for adults with DLD is needed if we are to better support the mental health and wellbeing of adults with DLD.…”
Section: Discussionmentioning
confidence: 99%
“…remembering and carrying out tasks to be completed at a later time point like attending a meeting or attaching a document to an email) compared to adults without dyslexia. Difficulty in reconciling neurocognitive differences may partially explain low work self-efficacy (Nalavany et al, 2018), decreased job satisfaction (de Beer et al, 2022), and an assortment of negative work-related emotions, including anxiety, depression, frustration, and exhaustion (de Beer et al, 2014;de Beer et al, 2022;McNulty, 2003;Nalavany et al, 2018;Wissell et al, 2022) among working AWD.…”
Section: Academic and Workplace Settingsmentioning
confidence: 99%
“…Not fitting in with mainstream society's expectations of success (e.g. educational and occupational competence) combined with the social misconceptions of dyslexia have been associated with experiences of discrimination and feelings of being judged, patronized, inadequate, unsupported, and shamed across postsecondary (Abbott-Jones, 2022;Denhart, 2008;Gant & Hewson, 2022;Jacobs et al, 2020;Lithari, 2018Lithari, , 2023Livingston et al, 2018) and workplace (de Beer et al, 2014;de Beer et al, 2022;Deacon et al, 2020;Kirkegaard, 2022;Wissell et al, 2022) contexts. In other words, negative emotional consequences experienced by AWD (e.g.…”
Section: Social Environmentmentioning
confidence: 99%
“…Australian and international research has identified that people with dyslexia work across a range of sectors, and skill levels [25][26][27][28][29][30]. Accordingly, many employers may find themselves in the position of supervising employees with dyslexia in their workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many employers may find themselves in the position of supervising employees with dyslexia in their workplace. Given the expected trajectory of difficulties related to reading, spelling, and writing, individuals with dyslexia are at increased risk of not meeting workplace demands or timeframes, despite having the training and/or qualifications to do so [30]. This is particularly evident if there is limited provision of suitable accommodations in the workplace [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%